Analisis Konsumsi Protein Hewani pada Rumah Tangga Indonesia - Umaroh, Rodhiah; Vinantia, Anggita (UI Scholars Hub, 2018)
Currently, animal protein consumption in Indonesia is still low. The consumption of animal protein is one of the keys to improving public health. This study aims to analyze the consumption of animal protein shown by consumption of meat, chicken, fish and milk commodities in households in Indonesia. Fifth Indonesia Family Life Survey (IFLS) data applied by model of Almost Ideal Demand System (AIDS). The results found that the own-price elasticity has a negative sign in accordance with the law of demand. Cross-price elasticity values vary from one another. Expenditure elasticity has positive sign indicates that all commodities are normal goods.